Performa Mesin Pencacah Pelepah Kelapa Sawit dengan Sistem Rotary - Yang Fitri Arriyani; Idiar Idiar; Subkhan Subkhan; Shanty Dwi Krishnaningsih (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
The utilization of palm frond waste can be processed as animal feed, compost, making briquettes, and basic materials for composite panels. The utilization of palm oil frond waste for various purposes is processed by chopping it into small chunks. The chopping process using a chopping machine makes it easy for farmers and speeds up the chopping time. Several studies have been carried out on the chopping process of palm leaf midribs using different motors and various models of cutting blades, varying motor power, and motor rotation speed in order to obtain the optimal engine capacity. The design method used in the manufacture of the machine is the Pahl Beitz method, namely planning, designing product concepts, designing shapes, and designing details. The parameters observed and measured were the effective capacity of the machine, the rendemen of the chopping, and the length of the chopping results. The trial was carried out three times by chopping the fronds each weighing 5 kg. The test results of machine showed that the average effective capacity of the machine was 244.06 kg / hour so that it was included in the class A category. The average chopping rendemen on the machine was 97% and the average size was count ? 50 mm is 89.5% and has met the requirements of SNI 7580: 2010.